Preparing for discharge of low-risk newborns to home care [Preparo de alta para o cuidado domiciliar de recém-nascidos de baixo risco] [Preparación de alta para el cuidado domiciliar de neonatos de bajo riesgo] - Fernanda Carla Pereira Duarte; Fernanda Garcia Bezerra Góes; Andrea Lyra Arnozo da Rocha; Joana de Andrade Nobre Ferraz; Juliana Rezende Montenegro Medeiros de Moraes; Liliane Faria da Silva (Revista Enfermagem UERJ, 2019)
Objective: to examine preparations for discharge of families in the rooming-in facility as regards home care for newborns. Method: this qualitative study research, conducted through Body Knowledge Creativity and Sensitivity Dynamics, as part of the Sensitive Creative Method, in 2017 and 2018, at a municipal hospital in the Rio de Janeiro coastal lowlands, with 17 participants, including puerperas and family members The resulting data were treated by thematic analysis. The study was approved by the research ethics committee. Results: preparation for discharge includes guidance mainly on breastfeeding and management of the umbilical stump, but also bathing, comfortable positions and vaccines. Nurses perform the social role of educators by circumstantial educational actions basically to convey information and demonstrate care for the newborn. Conclusion: in the preparation for discharge, there were gaps in essential guidance on safe, quality home care for newborns, and dialogical pedagogical approaches, taking the families’ realities as their point of departure, should be encountered.